Rethinking “Liberal Peacebuilding”: Conflict, Violence, and Peace in Mindanao - Miyoko, Taniguchi (Archīum Ateneo, 2019)
Conflict and violence have prevailed over the last four decades in conflict-affected areas in Muslim Mindanao, despite the signing of several peace agreements between the Philippine government and Islamic insurgents, and peacebuilding activities on the ground. Liberal or post-liberal peacebuilding theory—that emphasizes democratic institution-building, local politics and society, and hybrid possibilities for the transformation of both the “liberal” and the “local”—is not helpful in explaining why the Philippines, known as a liberal democratic state, is unable to bring about peace in Mindanao. From a historical perspective, the paper argues that conflict, violence, and peace in Mindanao should be analyzed through the lens of the tripartite relationship among the state, clan, and insurgents, taking into consideration local politics and the predominant customary governance structure instead of the simple dual relationship between the state and insurgents, and using the framework of the historical tripartite—a collaborative and cooperative relationship among three actors.